What causes neurodegenerative disease? - Armstrong, Richard (Folia Neuropathologica, 2020)
A hypothesis is proposed to explain the pathogenesis of neurodegenerative disease and the diversity of its phenotypes. The hypothesis is based on seven main propositions: 1) neurodegenerative disease is associated with multiple risk factors, 2) age is the most important of the risk factors, 3) aging differentially affects neuroanatomical pathways, 4) degeneration of these pathways results in the formation of pathogenic proteins, 5) pathogenic proteins spread along anatomical pathways, 6) the phenotypes of familial and sporadic forms of disease are similar and 7) neurodegenerative disease is characterised by heterogeneity, overlapping phenotypes, and multiple pathology. It is hypothesised that most cases of neurodegenerative disease are multifactorial in which interactions between external environmental and internal genetic risk factors act cumulatively over a lifetime to determine the ‘allostatic load’ of an individual. The allostatic load determines the rate of neural aging and results in the differential breakdown of neuro-anatomical pathways influenced by their relative use or disuse during life. The consequence is the formation of one or more pathogenic proteins, some of which may exhibit ‘prion-like’ behaviour and propagate through the brain from initial sites of formation along neuro-anatomical pathways to affect connected brain regions. Variations in the pathological proteins formed and their anatomical spread are ultimately responsible for the clinical and pathological diversity of disease phenotypes. Minimising the factors which contribute to the allostatic load over a lifetime and maximising cognitive and physical exercise may be necessary to reduce the incidence of neurodegenerative disease.